1996
DOI: 10.1107/s0021889896000684
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting oscillatory Bragg peak positions

Abstract: This work describes a detector‐fixed method in which X‐ray photons are collected on different points of the sensitive area of the detector without movement of the detector and which is suitable for measuring a single‐crystal orientation using (ω, ϕ) rotations. This method was used to determine the orientation of a silicon wafer whose (100) plane makes a small angle (misorientation angle) with the surface. ω scans of the 400 reflection were measured as a function of ϕwhile χ and 2θ were fixed at 0 and 69°, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…As a comment, the values of ( ) tend to be close to the horizontal line parallel to the flat surface and cutting plane of two Si wafers, which have different orientations, (111) and (004), as used by Dragoi (1992). As we can see, the angle ' tends to be close to 3.5 on (111) Si wafers and about 1 on (004) Si wafers.…”
Section: Testing Equations With Data From the Literaturementioning
confidence: 56%
See 4 more Smart Citations
“…As a comment, the values of ( ) tend to be close to the horizontal line parallel to the flat surface and cutting plane of two Si wafers, which have different orientations, (111) and (004), as used by Dragoi (1992). As we can see, the angle ' tends to be close to 3.5 on (111) Si wafers and about 1 on (004) Si wafers.…”
Section: Testing Equations With Data From the Literaturementioning
confidence: 56%
“…1 and 2 are the unknowns in the system of equations (1) and (2) found earlier by Dragoi (1992). Beyond the derivation of equations (1) and (2), given in Dragoi (1992), we mention that for a parallel family of planes of an object we need two parameters to characterize the surface orientation. We found that the two parameters to characterize the surface orientation of single crystals are and , the two unknowns of equations (1) and (2).…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations